Wpływ zarządzania zasobami ludzkimi na obsługę klientów Poczty Polskiej S.A. - Kurnal, Sylwia (My University, 2012)
Przedmiotem pracy licencjackiej jest przedstawienie istniejącego systemu zarządzania zasobami ludzkimi w Poczcie Polskiej S.A. oraz ukazanie odpowiedzi, jaki ma ono wpływ na obsługę klienta. Ukazano funkcje zarządzania zasobami ludzkimi mające wpływ na obsługę klienta. Badania ankietowe przeprowadzono wśród pracowników Urzędu Pocztowego w Zakopanem. Z przeprowadzonych badań wynika, że system zarządzania zasobami ludzkimi w Poczcie Polskiej S.A. ma pozytywny wpływ na obsługę klienta w urzędach pocztowych. Wyniki pokazują również, że pracownicy posiadają wiedzę na temat systemu zarządzania zasobami ludzkimi w Poczcie Polskiej S.A. i pozytywnie go oceniają.

The subject of the thesis is to present the existing human resources management system in the Polish Office S.A. and to illustrate the impact on customer service. The thesis shows the function of human resources management and subsequent impact on customer service. The surveys were conducted among the employees of the Post Office in Zakopane. The study shows that the human resources management system in Polish Post Office S.A. has a positive impact on customer service in all post offices. The results also show that the employees have the knowledge of human resources management system in Polish Post Office S.A. and evaluate it positively.
The impact of human resource management on customer service in the Polish Post Office S.A.
Keywords: zarządzanie; personel; obsługa klienta; rozwój; ankieta; management; staff; customer service; development; survey